2010
DOI: 10.1111/j.1651-2227.2010.01761.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anaesthetic agents administered to the mothers on transcutaneous bilirubin levels in the neonates

Abstract: The route of delivery had no effect on TBL. While bupivacaine was found to have no effect on neonatal bilirubin levels, levobupivacaine increased neonatal biluribin levels, but further studies are needed for definite results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Most of the previous studies investigated the effects of anesthesia in C/S groups (5-7). The studies including vaginal delivery for which anesthetic agents were not applied as a control group were extremely rare (8). In this study, a significant difference for sevoflurane and bupivacaine hydrocholoride -but not for prilocaine hydrocholoride -compared to vaginal delivery without anesthesia was observed.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Most of the previous studies investigated the effects of anesthesia in C/S groups (5-7). The studies including vaginal delivery for which anesthetic agents were not applied as a control group were extremely rare (8). In this study, a significant difference for sevoflurane and bupivacaine hydrocholoride -but not for prilocaine hydrocholoride -compared to vaginal delivery without anesthesia was observed.…”
Section: Discussionmentioning
confidence: 72%
“…Phuapradit et al have shown the absence of a correlation between C/S and neonatal hyperbilurubinemia by (11). Recently, Alkan et al have emphasized that the route of delivery had no effect on neonatal transcutaneous bilirubin levels during the first 24 hours of life (8). However, Gale et al reported a significant correlation between C/S and increased bilirubin levels (12).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations